Some q-Supercongruences from a Quadratic Transformation by Rahman - Liu, Yudong; Wang, Xiaoxia (Resultate der Mathematik, 2022)
Inspired by the recent work on q -congruences and a quadratic transformation formula of Rahman, we provide some new q -supercongruences. By taking parameters specialization in one of our results, we obtain a new Ramanujan-type supercongruence, which has the same right-hand side as Van Hamme’s (G.2) supercongruence for p ≡ 1 ( mod 4 ) . We also formulate some related challenging conjectures on supercongruences and q -supercongruences.